Naughty Nuns and Saucy Sisters: The Queer Nun at the End of the 1980s - Thomas Elliott (British Art Studies)
Whether on the front line of protests or on the gallery wall, the nun was a figure with a queer appeal for artists and activists at the end of the 1980s. But what inspired queer people in late twentieth-century Britain to get the habit? In this article I examine the queer nun as she appears in the activism of the London House of the Sisters of Perpetual Indulgence, an activist group and order of gay male nuns, and in the photographic sequence *Celestial Bodies* (1990), produced by Jean Fraser for the touring exhibition *Stolen Glances: Lesbians Take Photographs* (1991). Situating these as part of the political and religious atmosphere of the period, I examine how the queer nun allowed Fraser and the London House to challenge and critique the political realities of their era. By placing these works alongside sources drawn from British art of the eighteenth and nineteenth centuries, I examine the place of the nun in visual culture in Britain, particularly her representation as a licentious and sapphic figure, before returning to the twentieth century to trace the trans-historical resonances of these connotations in the work of Fraser and the London House and their attempts to deconstruct and reappropriate socially constructed categories of sexuality and gender.